Proving that China has a Profession of Engineering: A Case Study in Operationalizing a Concept Across a Cultural Divide. - Davis, Michael; Zhang, Hengli (Science & Engineering Ethics, 2017)
This article assumes that a profession is a number of individuals in the same occupation voluntarily organized to earn a living by openly serving a moral ideal in a morally-permissible way (a discipline) beyond what law, market, morality, and public opinion would otherwise require. Our question is whether the concept of profession (so defined) may have a far wider range than the term, so that, for example, pointing out that a certain language lacks a word for 'profession' in our sense, is not enough to show that those who speak the language also lack the concept. We believe the survey of 71 Chinese reported here begins to answer that question. This article has four parts. The first describes who was interviewed, how, when, and so on. The second describes some important features of the survey's questions, explaining how the questions track the concept of profession. The third part reports and interprets the results relevant to our question. The forth defends a tentative answer to the question with which we began-arguing the survey supports the claim that China has a profession of engineering. This article should serve as a 'proof of concept', that is, a model for similar studies around the world both of engineering and of other occupations thought to be professions.